Enterprise content management in cultural heritage institutions: A study of Sharjah landscape, United Arab Emirates - Zidan, Ahmed Adel; Boufarss, Mohamed (Digital Theory, Culture & Society, 2024)
This study examines the landscape of digital content management within heritage institutions in Sharjah, United Arab Emirates. It aims to evaluate the state, characteristics, and roles of these processes in preserving and promoting cultural heritage in the digital sphere. Utilizing a descriptive analytical approach, the research employs a checklist as the primary data collection instrument to investigate existing policies, plans, systems, and projects. Findings highlight the absence of formalized content management strategies in most institutions, which rely on unwritten, tacit policies. This lack of structured frameworks adversely impacts communication, operational performance, service delivery, and the long-term sustainability of their work. The study underscores the need for institutions to develop clear, written strategies and policies for digital content management and to conduct regular evaluations using metrics such as stakeholder feedback, statistics, and surveys. As the first study of its kind in the UAE, it provides a foundational understanding of digital content management practices in heritage institutions and offers actionable recommendations for policy and strategy development. The findings are expected to shape future practices, fostering improved digital preservation and accessibility of cultural heritage.